Modernization of the modern methodical system of physical education of students of agrarian universities - Griban G.P (Kharkov National Pedagogical University, 2012)
The model of the methodical system of physical education of students of agrarian universities is considered. A model is united by the aggregate of components of integral pedagogical process - from aims to end-point. A model is oriented to personality of future specialist-agrarian. Author conception, which leans against bases of theory and method of physical education, theory of professional preparation of specialists of physical culture, idea of integration of all of the tools of the integral system of preparation of specialist to the vital functions, is presented. The new methodical system is based on principle "athletic-health-improvement education and motive activity during all of life". Theoretical bases of forming of the methodical system of physical education of students are selected. The levels of functioning of the system are set. The levels of its functioning, motivative, organizational, procedure and active, diagnostic components have been established.